(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: This study aims to analyze the ketogenic diet that slows down weight gain in juvenile Mus musculus induced with benzopyrene (BZP). Method: Thirty-six female mice (Mus musculus), 6-8 weeks old, weighted 15-25 grams were divided into six groups randomly. K1 (negative control, standard diet) induced with oleum olivarum, while K2 (positive control, standard diet), P1 (ketogenic diet 1), P2 (ketogenic diet 2), P3 (ketogenic diet 3) and P4 (ketogenic diet 4) induced with BZP subcutaneously in the right breast at a dose of 0.3mg/20gBB/day for 14 days. The ketogenic diet was given for the next 28 days. Data were analyzed using the ANOVA and post hoc LSD test. Results: After 42 days, the ketogenic diet mice experienced slower weight gain (p=0.000) because BZP induced neurotoxicity and the administration of the ketogenic diet in juvenile mice induced neurohormonal changes. The ketogenic diet increased ketone plasma level (p=0.000) and reduced blood glucose levels (p=0.002) due to nutritional ketosis state. Conclusions: The ketogenic diet with fat:protein ratio 60:30 slows down weight gain, increased ketone levels and decreased blood glucose levels in juvenile mice with BZP as cancer inducer.